Shared Meanings or Missed Opportunities? The Implications of Functional Health Literacy for Social Marketing Interventions - Kemp, Gill; Eagle, Lynne (Marketing & Menedzsment, 2019)
Social marketing is being hailed as a key tool to help address the myriad health and overall population wellbeing issues facing societies. There is considerable evidence of the success of some specific social marketing interventions but a factor often overlooked is that literacy problems within a considerable proportion of the population means that the information provided may not be readily comprehended by all members of the target population. A study of the readability of a range of UK health information sources is reported. The paper concludes with a recommendation for further research in the area and for immediate improvement to social marketing-related activity.